Some Pathological Study of Experimental Infection of Blastocystis hominis in Mice - AL-Taee, E. H. (The Iraqi Journal of Veterinary Medicine, 2003)
Blastocystis hominis isolated from patients suffering from diarrhea patients (56) in number visited two hospital in Baghdad were cultured on liver infusion broth to infecting laboratory animals. Albino mice (4-6) wks in age were infected with Blastocystis hominis by inculcation and after the appearance of clinical signs (weakness, diarrhea) the mice were killed and pathological studies were done on organs like intestine, stomach and liver, the lesion showed desquamation of mucosa, severe infiltration of inflammatory cells specially around the parasite, this lesion was more severe in large intestine from the other organs. The parasite was seen in liver cells and appeared with different stages of growth and replication causing vaculation and necrosis in the hepatocyte.